2007
DOI: 10.1093/humrep/dem323
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of the human inhibin   subunit variant A257T and its potential role in premature ovarian failure

Abstract: BACKGROUND: A nucleotide substitution in the inhibin a subunit (INHA 769G>A, A257T) has been associated with premature ovarian failure (POF). We hypothesize this mutation causes a reduction in inhibin bioactivity, removing its suppression on the pituitary FSH secretion. The aim of this study is to establish if A257T inhibin has reduced bioactivity. METHODS: Mouse LbT2 pituitary gonadotrope, human granulosa (COV434) and human embryonic kidney (HEK293) cells were co-transfected with an activin-responsive reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 64 publications
0
16
0
Order By: Relevance
“…The functional significance of this amino acid change has recently been reported (44). The alanine-to-threonine change occurs within the putative receptor-binding region of the mature peptide.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The functional significance of this amino acid change has recently been reported (44). The alanine-to-threonine change occurs within the putative receptor-binding region of the mature peptide.…”
Section: Figurementioning
confidence: 99%
“…The alanine-to-threonine change occurs within the putative receptor-binding region of the mature peptide. Therefore, it appears that the change would impair the binding of inhibin to its receptor, resulting in an inability to activate subsequent signal transduction (29,44).…”
Section: Figurementioning
confidence: 99%
“…Most of these mutations involve the propeptide region and lead to a defective production of bioactive protein, providing further support for their implication in the development of POF. Moreover, inhibin-A is one of the most important regulators of the female reproductive cycle [102], and one mutation in the INHA (inhibin α) gene has been identified in patients with POF, resulting in an inactive mutant protein (A257T).…”
Section: Reproductive Disordersmentioning
confidence: 99%
“…POF is typically characterized by hypergonadotropism with circulating levels of follicle-stimulating hormone (FSH) in the postmenopausal range, and in some patients, at levels greater than 30 mIU/ml (29). Functional analysis of the inhibin ␣-subunit A257T variant revealed impaired inhibin B bioactivity and elevated FSH levels (30). Others have reported that the N-terminal fragment of the inhibin ␣-subunit has biological function (31).…”
mentioning
confidence: 99%